Perataan Jumlah Tenaga Kerja pada Proyek Perencanaan Pembangunan Guest House dengan Microsoft Project - Febriani, Febriani; Pratiwi, Reno; Devi, Suheriah Mulia (Universitas Batanghari Jambi, 2025)
Labor leveling in construction projects is a crucial strategy to optimize resources, improve work efficiency, and reduce excessive workforce fluctuations. However, this aspect is often overlooked due to the project's primary focus on timely completion rather than efficient labor utilization. This study aims to analyze the effectiveness of labor leveling in enhancing construction project efficiency. The method used is a case study of a Guest House construction project in Balikpapan with a total area of 1,514.875 m² and a duration of 308 calendar days. Microsoft Project was used to perform resource leveling through task rescheduling. The results showed that before leveling, the maximum number of workers reached 157 with uneven distribution. After leveling, the peak workforce was reduced to 125 workers, with the highest concentration occurring in week 15. Although it had no direct impact on labor wages, the implementation of leveling successfully reduced transportation and accommodation costs from Rp 1,886,830,000 to Rp 455,569,000. Therefore, labor leveling is proven to improve project efficiency and reduce potential resource waste in construction projects.